Pengaruh Kualitas Pelayanan, Citra Perusahaan, dan Kepercayaan terhadap Kepuasan Nasabah - Partawan, I Gede Adi; Wimba, I Gusti Ayu; Swara, Ni Nyoman Adityarini Abiyoga Vena (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of carrying out this activity is to find out the influence of service quality, company image and trust on customer satisfaction at PT Asuransi Ramayana Tbk Denpasar Branch. This activity uses multiple regression analysis tools to find the relationship between the independent and dependent variables. The large population here includes all individual customers of PT Asuransi Ramayana Tbk Denpasar Branch, totaling 1,215 customers. The sampling method in this research used the Slovin formula to find the appropriate number of samples, namely 92 samples. Here, people who have been determined to be the sample are given a questionnaire to obtain primary data. The research results show that service quality can make a very definite change in customer satisfaction at PT Asuransi Ramayana Tbk Denpasar Branch. The company image can make a very definite change in customer satisfaction at PT Asuransi Ramayana Tbk Denpasar Branch. Trust can make a very definite change in customer satisfaction at PT Asuransi Ramayana Tbk Denpasar Branch and service quality, company image and trust can make a very definite change in customer satisfaction at PT Asuransi Ramayana Tbk Denpasar Branch.